Developing a physiologically based pharmacokinetic model of apixaban to predict scenarios of drug–drug interactions, renal impairment and paediatric populations. Issue 8 (5th May 2021) - Xu, Ruijuan; Tang, Hong; Chen, Lin; Ge, Weihong; Yang, Jin
Abstract : Aims: To develop a physiologically based pharmacokinetic (PBPK) model for apixaban, an oral anticoagulant with a narrow therapeutic index, and to predict PK profiles and potential drug–drug interactions (DDIs) in patients with renal impairment and paediatrics. Methods: A whole‐body apixaban PBPK model was developed and validated in SimCYP for healthy adults with or without interacting drugs. The model was extended to renal impairment and paediatrics. Observed PK data in adults were compared with predicted data. The effect of renal function, age and DDIs on apixaban PK was investigated. Results: The PBPK model successfully predicted the PK of apixaban alone and under the influence of interacting drugs. For patients with renal impairment, the PBPK model successfully predicted the fold change in each impairment group; inhibitory DDI and renal impairment had a synergistic effect on the increase of apixaban exposure (e.g., almost 3‐fold increase of AUC in ketoconazole + severe renal impairment group). For infants younger than 1 year, the exposure of apixaban decreased with increased weight‐normalized clearance. For newborn infants, AUC of apixaban was >2‐fold higher than that in children older than 1 year. Meanwhile, the effect of DDI seems to be weakened while the effect of renal impairment might be enhanced in infants younger than 1 year. Conclusion: Our study provides a reasonable approach to estimate the dose adjustment for the first use of apixaban in special populations with complex situations, which has the opportunity to make the clinical practice much safer.